Kanalizacja bytowo-gospodarcza na przykładzie miejscowości Jemiołów. Część I. Zasady obliczania sieci = Sewage system for the Jemiołów village. Part I. Network calculation principles - Fruzińska, Róża (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper has beem described rules for calculating the existentiallyeconomic sewer the example of Jemiołów village. It also presents the principles of hydraulic calculations, drains recess, declines in sewers and wastewater flow. Presented also part of the calculation existentiallyeconomic drains for the selected village.
Keywords: kanalizacja bytowo-gospodarcza; kanalizacja - obliczenia; existentially-economic drains; sewer calculations